Introduction to the Musical Composition “Telung Benang” | Pengantar Komposisi Karawitan “Telung Benang” - I Wayan Agus Andika; I Komang Sudirga; I Wayan Sudirana (GHURNITA: Jurnal Seni Karawitan, 2022)
Telung Benang's musical artwork is inspired by the concept of rwa bhineda. Rwa bhineda is the balance of human life in a dualistic dimension, namely believing in the existence of two very powerful forces. This duality dimension concerns the difference between high-low, black-and-white, narrow-broad, and so on. The purpose of the creation of Telung Benang's artwork is to highlight two contradictory but interrelated characters (duality) into the musical language with the title of Telung Benang's work. Telung Benang is a term for numbers in Balinese which means seventy-five (75). Telung Benang is used as a title that will be realized with the concept that has been made, namely the pelog tone (7) and the slendro tone (5) combined to produce different colors and sound harmonies. The method of creating Telung Benang's works is arranged through three stages of creation, namely exploration, improvisation, and formation. Structurally, Telung Benang's work is divided into two parts. The division is done because it is based on the concept of duality which aims to highlight two parts that have different characteristics or colors (contrast) in one piece of music. This is what is meant as a typical reflection of the concept of dualism.